ENGLISH BLENDING WORDS FOUND IN â€œTHE JAKARTA POSTâ€ E-NEWSPAPER (PANOPTICON: Journal of English Studies, 2022)
This study entitled â€œEnglish Blending Word Found in The Jakarta Post    E-Newspaperâ€ presents the process of created the words by using blending process. This study also identified the types of blending word. The study methodology used in this study was the qualitative approach by analysing the data source taken from the                    e-newspaper. To analyse this study, theory from Naghmeh Mirzaie Hosseinzadeh (2014) used. The formed of blending word shows the creativity of human in creating of a word or language. Based on the analysis, it was found 19 data with 16 data of new blending clipping and 3 data of new blending with overlapping. The dominant types of blending word used are new blend with clipping: the first part of the first word is blending with the last part of the second word. Furthermore, it is hoped that this study could give benefit for English department students. Keywords: Word Formation, English Blending Words, The Jakarta Post